The Roles of Microtubule-Based Transport at Presynaptic Nerve Terminals - Yagensky, Oleksandr; Kalantary Dehaghi, Tahere; Chua, John Jia En (Frontiers in Synaptic Neuroscience, 2016)
Targeted intracellular movement of presynaptic proteins plays important roles during synapse formation and, later, in the homeostatic maintenance of mature synapses. Movement of these proteins is mediated by motor complexes travelling along intracellular cytoskeletal networks often in the form of vesicular packages. Presynaptic protein transport by kinesin motors in particular plays important roles during synaptogenesis to bring newly synthesized proteins to establish nascent synaptic sites. Conversely, movement of proteins away from presynaptic sites by dynein motors enables synapse-nuclear signaling and allows for synaptic renewal through degradation of unwanted or damaged proteins. Remarkably, recent data has indicated that synaptic and protein trafficking machineries can modulate each other’s functions. Here, we survey the mechanisms involved in moving presynaptic components to and away from synapses and how this process supports presynaptic function.